Structure of regional dykes and local cone sheets in the Midhyrna-Lysuskard area, Snaefellsnes Peninsula (NW Iceland) - TIBALDI, ALESSANDRO; BONALI, FABIO LUCA; CAVALLO, ALESSANDRO; Pasquaré, FA; Rust, D; D’Urso, A. (Bulletin of Volcanology, 2013)
This paper provides the first detailed structural description of 48 vertical dykes, 384 inclined sheets and two large intrusions and the geometry (strike, dip direction and dip) of 1116 fractures in the central area of the Snaefellsnes peninsula, NW Iceland. Our data show a more complex setting than that depicted by the WNW-ESE en-echelon trend of the volcanic structures at the surface. In the Miocene basement lavas, dykes dominantly strike N50–100°E whereas other directions are also present with a higher dispersion. Two main swarms of centrally dipping sheets have also been recognized, focussing towards two areas. Sheet dips range from 2 to 75° with the higher frequency between 10 and 45°. In section view, there is no systematic variation of sheet dip with distance from the focus area. Gabbro and granophyre laccoliths are present in the studied area but cross-cutting relations indicate that most of the inclined sheets are younger. Comparison with regional tectonics suggests that the N50–80°E-striking dykes are coherent with emplacement under the stress field of the pre-6 Ma Snaefellsnes Rift dominated by a NNW-SSE-directed least principal stress (!3). The N80–100°E dykes and the late Quaternary WNW-trending subaerial volcanic features are instead consistent with the development of a more recent E-W, right-lateral shear zone affecting the Snaefellsnes peninsula. Coherent sets of fractures have also been found. Within the inclined sheet swarms, the stress tensor rotated in response to an excess magma pressure linked to two underlying magma chambers of lobate shape, located at an estimated depth of about 400 and 500 m below sea level. This local magmatic stress also produced the centrally inclined fracture swarms that have been found in this area.